Effects of calcination temperature on grain growth and phase transformation of nano-zirconia with different crystal forms prepared by hydrothermal method - Yunchao Zhao; Liujie Xu; Mingyi Guo; Zhou Li; Zhaoning Xu; Jiahao Ye; Wuhui Li; Shizhong Wei (Journal of Materials Research and Technology, 2022)
The nano-Zirconia powders doped with different yttrium content (YSZ) were prepared by hydrothermal method, and then calcined in the atmosphere. The grain growth kinetics and mechanism of YSZ powder were analyzed. The addition of Y2O3 can refine the zirconia grains, and the mechanism of its action is discussed, and the grain sizes of the hydrothermal nano-powders (0, 3 and 11 YSZ) prepared with different Y2O3 are 15.4, 13.7 and 8.0 nm, respectively. The phase transformation mechanism of 3 YSZ powder and the influence mechanism of Y2O3 doping in different stages on powder growth are discussed. The growth mechanism of powder in different stages is analyzed and expounded. The first stage grain growth mechanism of 3 YSZ and 11 YSZ powders is dominated by surface diffusion and grain boundary rotational polymerization growth mechanisms, while the second stage grain growth is dominated by lattice diffusion and grain boundary migration polymerization growth mechanisms.